2022
DOI: 10.3390/ijerph19031887
|View full text |Cite
|
Sign up to set email alerts
|

Depressive and Sexual Disorders during the First and Second Wave of the COVID-19 Pandemic among Young Polish Women

Abstract: We investigated whether long-term social restrictions and COVID-19 exposure have different impacts on the mental and sexual health of Polish women compared to the effects experienced at the beginning of the pandemic. An online survey was conducted among Polish women via Facebook groups. The Beck Depression Inventory (BDI) and Female Sexual Function Index (FSFI) scores were compared for the first wave (April–May 2020) and the second wave (November 2020 to February 2021) of the pandemic. We enrolled 1644 partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Various studies carried out this past year have gone on to show that female students and those who were living in rural areas in particular, manifested higher levels of stress and depression as they had a fear of losing out in their academic year [ 3 , 12 ]. A study by Szuster [ 13 ], also highlighted the plight of young women whose depressive symptoms and fear intensified with subsequent lockdowns. Furthermore, the overnight change to online learning platforms coupled with a lack of information technology knowledge amongst non-technical educators also caused frustration among students [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies carried out this past year have gone on to show that female students and those who were living in rural areas in particular, manifested higher levels of stress and depression as they had a fear of losing out in their academic year [ 3 , 12 ]. A study by Szuster [ 13 ], also highlighted the plight of young women whose depressive symptoms and fear intensified with subsequent lockdowns. Furthermore, the overnight change to online learning platforms coupled with a lack of information technology knowledge amongst non-technical educators also caused frustration among students [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“… 49 Although a study showed that during COVID-19 pandemic female sexual dysfunction did not differ, depressive symptoms and fear intensified. 50 Most data showed that the COVID-19 pandemic significantly impacted mental and sexual health. 49 51 They stated that the difference in libido during the COVID-19 lockdown might be not feeling well or less interest in sexual intercourse.…”
Section: Discussionmentioning
confidence: 99%
“…Several papers have been published worldwide in the last two years on the impact of the pandemic on sexual relations, but they have mostly focused on one time point, usually the first months. Only a few national (and, in the light of available knowledge, also foreign) papers already published deal with cross-sectional studies repeated during the pandemic [ 34 ]. There are also a few very unique longitudinal studies [ 5 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A significant number of the above components of sexual life were analyzed in relation to the pandemic period [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The contributions came from various countries, including Poland [ 19 , 25 , 29 , 30 , 31 , 32 , 33 , 34 ], sometimes based on multi-country projects [ 8 , 23 , 35 ].…”
Section: Introductionmentioning
confidence: 99%